Design, synthesis and biological evaluation of (2S, 3R, 4R, 5S, 6R)-5-fluoro-6-(hydroxymethyl)-2-aryltetrahydro-2H-pyran-3, 4-diols as potent and orally active SGLT dual inhibitors. Issue 21 (15th November 2018) - Xu, Guozhang; Gaul, Michael D.; Kuo, Gee-Hong; Du, Fuyong; Xu, June Zhi; Wallace, Nathaniel; Hinke, Simon; Kirchner, Thomas; Silva, Jose; Huebert, Norman D.; Lee, Seunghun; Murray, William; et al.
Graphical abstract: Highlights: A new series of SGLT1 and SGLT2 dual inhibitors were disclosed. Two methods were developed to efficiently synthesize C5 -fluoro-lactones3 and4 . Lead compound2b demonstrated potent hSGLT1 and hSGLT2 inhibition. Lead compound2b showed robust in vivo efficacy in rodent models of diabetes. Abstract: A new series of (2S, 3R, 4R, 5S, 6R)-5-fluoro-6-(hydroxymethyl)-2-aryltetrahydro-2H-pyran-3, 4-diols as dual inhibitors of sodium glucose co-transporter proteins (SGLTs) were disclosed. Two methods were developed to efficiently synthesize C5 -fluoro-lactones3 and4, which are key intermediates to the C5 -fluoro-hexose based C-aryl glucosides. Compound2b demonstrated potent hSGLT1 and hSGLT2 inhibition (IC50  = 43 nM for SGLT1 and IC50  = 9 nM for SGLT2). It showed robust inhibition of blood glucose excursion in oral glucose tolerance test (OGTT) in Sprague Dawley (SD) rats and exerted pronounced antihyperglycemic effects in db/db mice and high-fat diet-fed ZDF rats when dosed orally at 10 mg/kg.